Advances on how to strengthen the peace within the Black Sea Region - Carmen Costea; Adrian Vasile; Larisa Mihoreanu; Adrian Vasile (Annals of Spiru Haret University Economic Series, 2016)
The reason/motivation for addressing issues related to the Black Sea region is multifaceted and requires adequate explanations which will be refereed to here from Romania’s perspective as, a Black Sea area country by geography, historical background, cultural and social characteristics, is the bridge of economic and cultural changes, peace stability and military safety. Its economy and standard of life is sensible to the various factors and trends originating in the region.